2010
DOI: 10.1007/s13142-010-0009-8
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of varenicline and three different behavioral treatment formats for smoking cessation

Abstract: There is a lack of evidence of the relative cost-effectiveness of proactive telephone counseling (PTC) and Web-based delivery of smoking cessation services in conjunction with pharmacotherapy. We calculated the differential cost-effectiveness of three behavioral smoking cessation modalities with varenicline treatment in a randomized trial of current smokers from a large health system. Eligible participants were randomized to one of three smoking cessation interventions: Web-based counseling (n=401), PTC (n=402… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 58 publications
0
19
0
1
Order By: Relevance
“…The 61% respondent and 38% ITT penalised imputation (missing=smoking) 30-day point prevalence quit rates at 6 months in the standard treatment group indicated that tobacco users who receive a multiple-call phone counselling programme, have access to cessation medication benefits, and successfully achieve at least a 24 h abstinence period early in treatment do quite well. These quit rates are high compared to studies focusing on all commercial quitline enrolees (eg, 34.3–41.1% responder quit rate at 6 months 27 28 ). The relatively strong performance and engagement in standard treatment for this study may have made achieving improvements with a low intensity relapse prevention intervention even more challenging.…”
Section: Discussionmentioning
confidence: 74%
“…The 61% respondent and 38% ITT penalised imputation (missing=smoking) 30-day point prevalence quit rates at 6 months in the standard treatment group indicated that tobacco users who receive a multiple-call phone counselling programme, have access to cessation medication benefits, and successfully achieve at least a 24 h abstinence period early in treatment do quite well. These quit rates are high compared to studies focusing on all commercial quitline enrolees (eg, 34.3–41.1% responder quit rate at 6 months 27 28 ). The relatively strong performance and engagement in standard treatment for this study may have made achieving improvements with a low intensity relapse prevention intervention even more challenging.…”
Section: Discussionmentioning
confidence: 74%
“…Our study ICER of $2316 per additional smoker who quit for Medicaid recipients is similar to the cost-effectiveness of other tobacco use treatment options for smokers in general populations. For example, the ICER for varenicline combined with proactive telephone counseling has been estimated at $2600 per additional smoker who quits [40]. Our ICER results illustrate that incentivizing engagement with treatment counselors is a viable Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Approximately 1 in 6 life-long smokers will die from lung cancer, and death from premature heart disease is about 1 in 2 [41,42]. The quality adjusted life year for smoking cessation is less than $1500 [43]. If the cost of CT screening high-risk, current smokers is prohibitive, then it may be appropriate, in regard of cost effectiveness, to require smoking cessation prior to the pursuit of CT screening.…”
Section: Discussionmentioning
confidence: 99%